1997
DOI: 10.1021/bi9706778
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Mechanism for p38 MAP Kinase

Abstract: p38 has been shown to be a critical enzyme in the pro-inflammatory cytokine pathway and is a member of the mitogen-activated protein (MAP) kinase family. While the details for p38 activation and subsequent signal transduction have begun to be elucidated, little is known about the kinetic mechanism for p38. In this study, we have determined the kinetic mechanism for p38 MAP kinase. Data from initial velocity patterns in the presence and absence of a dead-end inhibitor and two triarylimidazole p38 inhibitors wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
102
6
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(118 citation statements)
references
References 18 publications
(37 reference statements)
8
102
6
2
Order By: Relevance
“…P38-α induces, while p38-β suppresses cell death [36]. SB203580 inhibits mainly α and β isoforms [37,38]. Because no significant suppression of p38 was detected by SB203580, γ and/or δ p38 isoforms may be predominantly expressed in SVHK cells.…”
Section: Discussionmentioning
confidence: 99%
“…P38-α induces, while p38-β suppresses cell death [36]. SB203580 inhibits mainly α and β isoforms [37,38]. Because no significant suppression of p38 was detected by SB203580, γ and/or δ p38 isoforms may be predominantly expressed in SVHK cells.…”
Section: Discussionmentioning
confidence: 99%
“…For cAMPdependent kinase Whitehouse et al (50,51) reported that the mechanism was ordered, with the nucleotide binding first while Cook et al (30) reported that MgATP and peptide bind randomly, although initial binding of the nucleotide is preferred. An ordered sequential mechanism has been reported for p38 MAPK (32), for the vascular endothelial growth factor receptor-2 tyrosine kinase (52) and for the v-Src kinase (53). Both an ordered (54) and a random pathway (55) have been reported for the EGF receptor tyrosine kinase.…”
Section: Table II Summary Of Kinetic Constantsmentioning
confidence: 95%
“…PD98059 23 (a specific inhibitor of ERK1/2), UO126 24 (a selective MEK inhibitor of ERK1/2 signaling) and SB203580 25 (a specific inhibitor of p38 MAPK) were added to the cells 1 hr before treatment with 100 lM EGCG plus 10 lM celecoxib: Pretreatments with PD98059 and UO126 dose-dependently reduced levels of phospho-ERK1/2 that were enhanced by cotreatment (Fig. 4a).…”
Section: Synergistic Induction Of Apoptosis By Cotreatment With Egcg mentioning
confidence: 99%